Internet Addiction as a Mode of Disembodied Existence - Kopteva, N. V. (Вестник Кемеровского государственного университета, 2022)
According to the prevailing clinical model of Internet addiction disorder, the symptoms of Internet addiction are not substantially different from the ones of other previously known behavioral and chemical addictions. In the present article we argue that this model significantly depsycholizes the phenomenon which stems from the mass use of information technologies providing access to cyberspace. We compare psychological characteristics of the Internet addiction to disembodiment, that is, lack of the physical body of an information technology user, first described by the media theorist M. McLuhan. Alongside anonymity, technological disembodiment is the inevitable consequence of the use of the Internet, and it is just as important in the formation of the addiction and accompanying disorders. But the phenomenon of virtual unsubstantial self which represents the manifestation of the Spirit Archetype in the realities of the digital society obviously exceeds anonymity in terms of importance and scope. Our theoretical model of the disembodiment on the Internet is based on the conceptions of ‘schizoid disembodiment’ and ‘unembodied self ’ by the British existential psychologist R. D. Laing. In particular, there is evidence to suggest likeness between the withdrawal from reality of a schizoid by way of ‘exit’ from their own physical body and the form of escapism specific to the Internet addiction in contrast to other addictions. Respective empirical constructs were measured and compared. We used the adapted version of the Chinese Scale by S.-H. Chen, which implements the clinical model of Internet addiction most consistently, and Disembodiment on the Internet Diagnostic Technique by N. V. Kopteva, A. Yu. Kalugin and L. Ya. Dorfman. The results indicate that with Internet addiction traditional symptoms of addictions correlate to the weakness of the divided self. This causes a range of problems aggravated by the ones caused by disembodiment, namely virtualization, de-realization of the self of a user and experience of illusiveness of existence. The data shows that dependence and disembodiment on the Internet may refer to a specific technological modus of a person’s existence within the information society.